The Oxford handbook of industrial policy - Oqubay, Arkebe; Cramer, Christopher (Professor of political economy); Chang, Ha-Joon; Kozul-Wright, Richard, 1959- (Oxford : Oxford University Press, 2020)
Written by leading international thinkers on the subject, 'The Oxford Handbook of Industrial Policy' pulls together different perspectives and schools of thought from neo-classical to structuralist development economics to discuss and highlight the adaptation of industrial policy in an ever-changing socio-economic and political landscape.
Introduction to Industrial Policy and Development / Arkebe Oqubay, Christopher Cramer, Ha-Joon Chang, Richard Kozul-Wright -- Greening Industrial Policy / John A. Mathews -- Globalization Narratives and Industrial Policy / Daniel E. Esser, James H. Mittelman -- Grand Challenges, Industrial Policy and Public Value / Mariana Mazzucato, Rainer Kattel -- The Political Economy of Development Financing / Jonathan Di John -- The Shifting 'Terrain of the industrial' and Digital Industrial Policy / Antonio Andreoni -- An Industrial Policy Framework to Advance a Global Green New Deal / Robert Pollin -- Industrial Policy and Gender Inclusivity / Stephanie Seguino -- Macro-policy, Labour Markets, and Industrial Policy / Servaas Storm -- Technical disruptions, GVC, and Industrial Policy / David Bailey, Lisa De Propris -- The Theory and Practice of Industrial Policy / Arkebe Oqubay -- Industrial Policy: A long term perspective and overview of theoretical arguments / Erik S. Reinert -- Post-war American Industrial Policy: How Dixie Won the Civil War / Michael H. Best -- European Industrial policy: A Comparative Perspective / Patrizio Bianchi, Sandrine Labory -- The European Union's Industrial Policy / Michael A. Landesmann, Roman Stöllinger -- Diverse Tools of Industrial Policy in Korea: A Schumpeterian and Capability-based View / Keun Lee -- Industrial Policy and Industrialization in Southeast Asia / Rajah Rasiah -- National Champions, Reforms and Industrial Policy in China / Chen Li, Muyang Chen -- Industrial policies in the BRICS / Fernando Santiago -- Industrial Policy, Macroeconomics and Structural Change / José Antonio Ocampo -- Successes and Failures of Industrial Policy in Transition Economies of Europe and Asia / Vladimir Popov -- Latin American Industrial Policies: A Comparative Perspective / José Antonio Ocampo, Gabriel Porcile -- Phases and Uneven Experiences in African Ind
Also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 2, 2020).
Keywords: Industrial policy